Teachers' Strategies for Implementing The Values of The Kerigan Tradition in Strengthening Students' Character at MTs Plus Al-Jawami Cilacap in 2025 - Nani Kurniasih; Mulyoto; A. Dardiri Hasim (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
This study examines teachers' strategies for implementing the values of the Kerigan tradition in strengthening students' character at MTs Plus Al-Jawami Cilacap in 2025. The research aims to identify the strategies employed by teachers, explore the character values embedded in the Kerigan tradition, and analyze their contribution to students' character development. This study employed a qualitative case study approach. Data were collected through observations, interviews with teachers, school leaders, and students, as well as documentation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that teachers integrate the values of the Kerigan tradition into classroom learning, religious activities, and school culture through modeling, habituation, guidance, and reflective evaluation. The tradition promotes essential character values, including cooperation, responsibility, discipline, respect, social awareness, and religious commitment. The implementation of these values has positively influenced students' attitudes and behaviors, as reflected in their increased participation in collaborative activities, improved discipline, and stronger sense of responsibility toward the school community. The study concludes that integrating local cultural traditions into educational practices provides an effective approach to character education by reinforcing moral values while preserving local cultural heritage.